PERSEPSI GURU DAN SISWA TERHADAP PENDIDIKAN OLAHRAGA DI SEKOLAH SD NEGERI 023897 BINJAI TIMUR KOTA BINJAIPERSEPSI GURU DAN SISWA TERHADAP PENDIDIKAN OLAHRAGA DI SEKOLAH SD NEGERI 023897 BINJAI TIMUR KOTA BINJAI - Salsabila Putri Wibowo; Suyono; Rini Anggraini Br Siregar; Putri Aulia Sitorus (STKIP Subang, 2024)
This research aims to identify and analyze teachers' and students' perceptions of sports education at SD Negeri 023897 East Binjai, Binjai City. The research method used is a quantitative descriptive method with data collection through questionnaires distributed to teachers and students. The research results show that both teachers and students have a positive view of the importance of sports education in students' physical, mental and social development. Teachers see sports education as an effective means of improving students' health and motor skills, as well as building discipline and teamwork. Meanwhile, students revealed that sports lessons were one of the subjects they liked the most because it provided the opportunity to be active and socialize. However, this research also found several obstacles such as a lack of adequate sports facilities and limited time for sports lessons in the curriculum. It is hoped that these findings can provide input for schools and policy makers to improve the quality of sports education in elementary schools.